A Study of Knowledge, Attitude, and Practice of Nasal Irrigation During the COVID-19 Pandemic - Riri Juliantika; Fiona Widya Sari; Rachmat Hidayat; Puspa Zulaika; Ziske Maritska (Natural Sciences Engineering and Technology Journal, 2022)
COVID-19 is a respiratory tract infection caused by the novel coronavirus (nCov). Nasal irrigation is one of the efforts to prevent COVID-19. Nasal irrigation is an act of flushing saline solution into the nasal cavity. This research aims to determine level of knowledge, attitudes, and practices of the community regarding nasal irrigation during the COVID-19 pandemic. This study was a descriptive observational study. The sample of this research was the people of Palembang who were eligible for the inclusion and exclusion criteria with the consecutive sampling technique as many as 398 respondents. Data were obtained through primary data in the form of questionnaires, processed using the SPSS program, and analyzed using univariate analysis. The majority of respondents were aged 18-25 years old (65.5%) and had senior high school 58.0%. The level of public knowledge about nasal irrigation during the COVID-19 pandemic was in the moderate category of 36.2%. The level of public attitudes regarding nasal irrigation during the COVID-19 pandemic was in the good category at 83.4%. The level of nasal irrigation practice was included in the bad category of 75.6%. In conclusion, the community of Palembang had moderate level of knowledge, a good level of attitude, and a bad level of practice regarding nasal irrigation during COVID-19 pandemic.